Pengaruh Antara Disiplin Kerja, Motivasi Kerja, Dan Lingkungan Kerja Pada Komitmen Organisasional Karyawan (Studi Di Waroeng Spesial Sambal Yogyakarta) Effect Between Work Discipline, Work Motivation, And Work Environment In Employee Organizational Commit - Risfanda Nurhudiana (EBBANK, 2019)
The purpose of this study is to describe the influence between work discipline, work motivation, and work environment simultaneously on employee organizational commitment. This research belongs to a type of causal associative research. The population is 80 employees of Waroeng Spesial Sambal Yogyakarta, and 45 employees are used as samples for sampling using accidental sampling. The method of data collection uses the questionnaire method, while the data analysis technique used is multiple linear regression analysis supported by F test, t test, R ^ 2 test, and classic assumption test. The results of this study that with 0.05 significance indicate work discipline, motivation work, and the work environment simultaneously influences simultaneously the employee's organizational commitment.